Seasonal Eff ects on Semen and Testosterone in Zebu and Taurine Bulls - Marcelo George Mungai Chacur (Acta Scientiae Veterinariae, 2013)
Background: In Brazil, a higher percentage of abnormal sperm after high temperature and relative humidity observed a higher semen volume in the rainy. The semen quality may be signifi cantly affected by environment, by fl uctuations in temperature, humidity and photoperiod. The objective of this study was to evaluate the seasons infl uence (spring, summer, autumn and winter) on semen characteristics and testosterone levels in Nellore and Simmental bulls raised on fi eld. Materials, Methods & Results: The city of Presidente Prudente-SP-Brazil, where the experiment was realize, presents latitude 21°29`50``S, longitude 49º14`2``W and altitude of 475 meters. In 2008/2009, the climatic factors measured for Spring - SP; Summer - SU; Autumn – A and the Winter - W were: average temperature (SP - 25.9; SU - 26.6; A - 21.9 and W - 21.1°C), stroke (SP - 400.9; SU - 464.0; A - 721.3 and W - 142.6 hours), cumulative rainfall (SP - 291.8; SU - 925,0; A - 273.0; and W - 191.8 mm) and average relative humidity (SP - 65.9; SU - 71.7; A - 70.1 and W - 66.7%). Five Nellore and fi ve Simmental bulls with 48-72 months old, extensively managed were evaluated for sexual soundness using physical and morphological characteristics of semen and testosterone serum levels. Sixteen semen samples by automatic electroejaculation were carried out in each of 10 bulls, totaling 160 samples. The experiment was conducted from September to August and made four harvests in each of the four seasons. The analysis of testosterone concentration (ng/dL) were performed with commercial kits and quantifi cation of the hormone made by radioimmunoassay (RIA) totalizing eight replicates per bull, 2 per season, totalizing 80 samples. Data on characteristics of semen and testosterone evaluation were subjected to analysis of variance, considering the study as a factorial experiment, and the differences between means compared by Tukey test at 5%. There was decreased motility and vigor semen (P < 0.05) during winter in Simmental bulls. There was correlation between serum testosterone (P < 0.01) to motility and vigor in Nellore and Simmental bulls. In relation to sperm morphology, major and total defects were different (P < 0.05) between breeds in the spring, with higher percentages observed in the Simmental breed. In the winter, for minor and total defects, there were differences between breeds (P < 0.05) being major to the Simmental. For the Simmental breed, there was difference (P < 0.05) between summer and winter seasons for the major sperm defects and total quality with better morphology in the summer. The sperm concentration, between breeds, in spring and autumn showed differences (P < 0.05), being higher for the Simmental. There was difference (P < 0.05) between breeds for testosterone, in the summer season. In the Simmental breed there was a signifi cant correlation between testosterone and semen characteristics, being mass movement (0.31), concentration (0.37) and total defects (-0.26). For t